2016
DOI: 10.1007/s00268-016-3788-3
|View full text |Cite
|
Sign up to set email alerts
|

Open Repair of AAA in a High Volume Center

Abstract: Early mortality after open repair of AAA in high volume center might be very low due to experienced multidisciplinary team. Centralized open aortic surgery might be solution for effective treatment of patients with unsuitable anatomy or for young patients with long life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…þ e e 5 (33) Nakamura (2009) 41 Caseecontrol e e þ e e NA NA e e e þ ? þ þ e 4 (31) Davidovic (2017) 42 Cohort þ e þ e e e ? e e e þ e þ e e 4 (27) Sharma (2006) 43 Caseecontrol e e e e e ?…”
Section: Included Studiesunclassified
“…þ e e 5 (33) Nakamura (2009) 41 Caseecontrol e e þ e e NA NA e e e þ ? þ þ e 4 (31) Davidovic (2017) 42 Cohort þ e þ e e e ? e e e þ e þ e e 4 (27) Sharma (2006) 43 Caseecontrol e e e e e ?…”
Section: Included Studiesunclassified
“…After 2003, EVAR became the treatment of choice for AAA, replacing OPEN as the most common surgical intervention for AAA repair. 33 Recently, Davidovic et al 34 showed that short-term mortality after OPEN surgical repair of AAA in high-volume centers with highly experienced anesthesiologic and surgical teams might be very low. Furthermore, in the same study, 34 OPEN improved clinical outcomes in patients with a hostile abdomen, unsuitable anatomy, or young patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 Recently, Davidovic et al 34 showed that short-term mortality after OPEN surgical repair of AAA in high-volume centers with highly experienced anesthesiologic and surgical teams might be very low. Furthermore, in the same study, 34 OPEN improved clinical outcomes in patients with a hostile abdomen, unsuitable anatomy, or young patients. However, this study 34 did not directly compare clinical outcomes with EVAR, as it only included patients undergoing OPEN.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional approach is represented by the open surgical repair-a longitudinal abdominal incision is performed; abdominal organs are eviscerated and aneurysmectomy is performed with subsequent aortic reconstruction. [5,6] In addition to this approach, a less invasive endovascular treatment has been proposed. Over the years, endovascular aneurysm repair (EVAR) has become the first treatment of choice in patients with suitable anatomy [7][8][9].…”
Section: Introduction Abdominal Aortic Aneurysm Definition and Treatment Optionsmentioning
confidence: 99%